Interaksi Pembelajaran Berbasis Rahmah, Optimalisasi Fungsi Otak untuk Belajar - Sari, Dewi Purnama; Sutarto, Sutarto (JOEAI (Journal of Education and Instruction), 2021)
This study aims to describe the interaction of al-Rahmah-based learning and its urgency in optimizing brain function for learning. The method used is library research. Sources of data obtained from the Koran, hadith, books and various scientific works that are relevant to the topics discussed. The data collection technique was carried out in three stages, namely editing, organizing and finding, then analyzed using content analysis and comparative analysis approaches. The results showed that al-Rahmah or affection-based learning interactions lead to secure attachment to students, thus creating a positive relationship between teachers and students. Positive relationships can cause positive emotions that can lead to hypothalamic-pituitary-adrenocortical stimulation or HPA hormones, maintaining the balance of the left and right brain so as to maximize brain function for learning. In conclusion, al-Rahmah-based learning interaction, learning with the application of the principle of compassion, creates a good relationship between teachers and students so that it has a positive effect in stimulating the optimization of students' brain functions for learning. Keywords: Learning interaction, Rahmah, Affection, Learning